USULAN PERBAIKAN PELAYANAN BENGKEL NISSAN HALIM DENGAN METODE SERVQUAL, IPA, DAN QFD - Aditia Yunanda (Universitas Mercu Buana, 2014)
Abstract. This thesis aims to measure the quality of services provided by NissanHalim. This study compares the levels of service according to the customer'sexpectations with the work done so far. The method used in this research isdescriptive analysis method qualitative data collection method through literaturestudy, observation and questionnaires. To determine the gap between perceptionand expectations of customers used the method ServQual. Results ServQual foundthat the quality of service provided does not meet customer expectations with thebiggest gap found on factors thoroughness of work performed servicing Todetermine the performance which need to be rectified used ImportancePerformance Analysis. Results IPA found that the factors completeness of theservice work performed, front linernya responsive, the operational time of theworkshop according to your schedule, as well as the reasonableness of the pricethat needs to be fixed. Meanwhile, to suggest improvements to the companyconducted method of Quality Function Deployment. QFD results provide thebenchmark improvement in the booking system, the number of technicians,service allocation, role play SA, service tools and technician skill that needs to beimproved so that the results could change science.Keywords: Service Quality, Customer Satisfaction, ServQual, IPA, QFD